Dispositivo estratégico, resistência e relações de poder: um ensaio sobre a identidade do Centro de Educação Matemática (CEM) e seu papel na (E)educação (M)matemática brasileira - Silva, Heloísa da [UNESP]; Garnica, Antonio Vicente Marafioti [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2012)
This paper presents some results of the investigation on the Mathematical Education Centre (CEM), a group of mathematics teachers’ educators in São Paulo, Brazil, acting mainly between 1984 and 1997. The essay, marked by an effort to constitute the identity of the CEM based on Foucault, assumes that the identity constitution process is not about what CEM is or was, but mainly about a set of possibilities of apprehending it from its historically contextualized strategies and initiatives. In this Foucauldian reading, which brings about concepts such as "strategic device", "resistance" and "power relations", the CEM constitution appears while it creates conditions for the constitution of Brazilian modern mathematical education.

Este artigo apresenta alguns resultados da investigação realizada sobre o Centro de Educação Matemática (CEM), um grupo de educadores matemáticos da cidade de São Paulo atuante principalmente entre os anos de 1984 e 1997. No ensaio, marcado por um exercício de constituir a identidade do CEM a partir de uma leitura foucaultiana, assume-se que o processo de constituição de identidades não se refere ao que o CEM é ou foi, mas a um conjunto de possibilidades de apreendê-lo a partir de estratégias e iniciativas historicamente contextualizadas. Nessa leitura foucaultiana, que traz à cena conceitos como "dispositivo estratégico", "resistências" e "relações de poder", o CEM é visto como constituindo-se ao criar condições para a constituição da moderna Educação Matemática brasileira.
Strategic device, resistance and power relations: an essay on the identity of the Mathematical Education Center (CEM in the Brazilian abbreviation) and its role in the Brazilian Mathematical Education
Keywords: Mathematical instruction; Identities; Foucauldian reading; Educação matemática; Identidades; Leitura Foucaultiana